PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA APARATUR SIPIL NEGARA MELALUI DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Dinas Perhubungan Situbondo) - Mashudi, Mukhlish; Tulhusnah, Lusiana; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2022)
An organization or company can be said to be successful if the employee's performance is in accordance with the expectations of the organization or company. Improvement of the performance of the State Civil Apparatus is always carried out in order to achieve the target of excellent service for the community. The purpose of this study was to analyze and examine the influence of organizational culture and motivation on the performance of state civil servants through work discipline as an intervening variable (Study at the Situbondo Transportation Service). This research is an explanatory research. The population in this study is the State Civil Apparatus of the Situbondo Regency Transportation Service. The sampling technique used a saturated sample. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that organizational culture has a positive but not significant effect on work discipline, motivation has a significant positive effect on work discipline, organizational culture has a significant positive effect on ASN performance, Motivation has a positive significant effect on ASN performance, Discipline work has a significant positive effect on the performance of ASN. The results of the indirect hypothesis test show that the organizational culture variable on ASN performance through work discipline has a positive but not significant effect, motivation on ASN performance through work discipline has a positive significant effect.